Current Practices and Insights on Supply Chain Risk Management in the Construction Industry: A Review - J.A Bamgbade; Sii Yu Ting; M.N.M Nawi (International Journal of Supply Chain Management, 2020)
This paper reviews the related studies on the current practices and insights in supply chain risk management within the construction industry. Articles published between 2000 and 2018 are classified and analyzed using simplified systematic literature review, which is performed through the material collection, category selection and literature matrix. While the research on supply chain risk management started relatively recently, much of these studies were generic and not contextualized for the construction industry. Construction supply chains risk treatment and monitoring phase require further attention, with inputs from all the supply chain actors in the upstream linkage. Only peer-reviewed journal articles were considered in this study. And it is hoped that the findings will serve as a guide to construction managers who would like to better understand how risks in the upstream and downstream linkages of construction supply chains are managed. We acknowledged that the implementation of construction supply chain risk management is immature, and there is a dearth of literature in this area. This study also identifies the risk management process currently practised in the industry and provides a framework for literature classification. The study identifies literature gaps that can provide opportunities for future research in the area of CSCRM. It also discusses future research directions in this area.